2010
DOI: 10.17221/1712-cjas
|View full text |Cite
|
Sign up to set email alerts
|

ANXA9, SLC27A3, FABP3 and FABP4 single nucleotide polymorphisms in relation to milk production traits in Jersey cows

Abstract: Milk components originating from blood plasma substrates are synthesized in epithelial cells of the mammary gland. Milk lipids are synthesized from fatty acids which bind to specific proteins – FABPs (fatty acid binding proteins). FABPs are a family of small cytoplasmic proteins; nine members of the family have been identified so far (FABP1–FABP9) (Chmurzyńska et al., 2006). Their main roles include fatty acid uptake, transport and metabolism. FABPs can modulate the fatty acid concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…It was suggested that the increased milk content of FFA in late lactation is associated with a poor energy intake at the end of the pasture season (September to November). Body fat deposits are mobilised, and FFA as a source of energy are released into the blood and transported into milk (Kulig et al 2010). The fat content and the fat/protein ratio in milk therefore belong among the most important indicators of energy balance in animals (Sojková et al 2010;Ducháček et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the increased milk content of FFA in late lactation is associated with a poor energy intake at the end of the pasture season (September to November). Body fat deposits are mobilised, and FFA as a source of energy are released into the blood and transported into milk (Kulig et al 2010). The fat content and the fat/protein ratio in milk therefore belong among the most important indicators of energy balance in animals (Sojková et al 2010;Ducháček et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…High milk yields and a limited ability of feed intake in early lactation trigger the process of lipomobilisation and the release of energy from the body fat reserves (Gonzáles et al 2011). As a result, the contents of fat and FFA increase both in blood and milk (Kulig et al 2010). Therefore, the content of FFA may indicate the health status of dairy cows (Hanuš et al 2004).…”
mentioning
confidence: 99%
“…[14][15][16] The studies of the relationship between polymorphism in the ANXA9 gene and the performance traits of milk have so far been carried out mainly in relation to dairy cattle, and the studied polymorphism is a substitution in exon 5 (position 951 A > G), resulting in a change in the amino acid sequence (H → A). [16][17][18][19][20] The work of Kulig et al 18 showed a statistically significant association of this polymorphism with the fat content in milk. The regression analysis presented by Martinez-Royo et al 20 showed a statistically significant impact of genotype (GG) on estimated breeding value for the fat content in cows' milk.…”
Section: Discussionmentioning
confidence: 97%
“…Limited information is available regarding the effect of FABP4 on milk production traits in livestock. In Jersey cattle, Kulig et al (2010) studied variation in two regions of the bovine FABP4 gene (from nucleotides 5433 to 6106 and from nucleotides 7417 to 7868), for the accession number AAFC01136716, and found no associations between the FABP4 polymorphism and daily milk yield, percentage fat content, or percentage protein content. For the same regions of FABP4 in Polish Holstein-Friesian cows, Kulig et al (2013) revealed a significant effect for the single-nucleotide polymorphism (SNP; c.328G > A) on the estimated breeding values for protein yield (P < 0.05) and percentage protein content (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%